Empowering Agriculture through Agro-Climate Advisory Services in Ethiopia: Agro-climate advisory for Training of Trainers (ToT) - Rettie, Fasil M; Mamo, Girma; Ndour, Adama (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This training manual focuses on Training of Trainers (ToT). It aims to equip them with the basic knowledge, skills, and communication channels framework required to disseminate effective agro-climate advisory (AgCA) services to smallholder farmers. The manual begins with the definitions and descriptions of AgCA, followed by the purpose, key objectives, and other essential components. It covers the basics of climate, including weather, climate variability, and climate change, as well as their impact on agricultural productivity. Recognizing the importance of establishing the value chain of partners and farming communities, the manual highlights participatory approaches and integrating local knowledge into actionable AgCA services in a comprehensive end-to-end manner.